Essentials of statistics for business and economics - Anderson, David R. (David Ray), 1941-; Sweeney, Dennis J.; Williams, Thomas A. (Thomas Arthur), 1944- (Cincinnati : South-Western College, 2000)
The book balances a conceptual understanding of Statistics with the real-world application of statistical methodology.
System requirements for accompanying computer disc: Microsoft Excel and Minitab.
Includes bibliographical references and index.
uaj 03/03/2015
Loan
Keywords: Social sciences -- Statistical methods; Commercial statistics; Economics -- Statistical methods; Statistics -- Problems, exercises, etc